Akar-akar Transnasionalisme Islam Hizbut Tahrir Indonesia (HTI) - Hilmy, Masdar (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
This paper tries to trace and analyze the roots ofâIslamic transnationalismâ or âtransnational Islamâ in Indonesia through the lens of the three theoretical frameworks that I borrowed from Mandaville as follows: (1) travelling theory; (2) hibridity theory, and; (3) diasphora theory. The paper focuses its analysis on an Islamic movement who carries the ideology of âIslamic transnationalismâ (khilâ fah Islâmiyah), namely Hizbut Tahrir Indonesia (HTI). Before delving into the details of HTIâs ideological roots of transnational Islam, however, a conceptual definition of âtransnational Islamâ will be elucidated in advance.